Modelling of underwater acoustic propagation over elastic, range-dependent seabeds - Koessler, Matthew Walter (Curtin University, 2016)
Research was conducted on the development of a numerical algorithm that can accurately model range dependent acoustic propagation over layered calcarenite seabeds that are typical around Australia. A seismoacoustic adiabatic normal mode algorithm was developed and tested against an existing seismoacoustic parabolic equation code, and also compared to measured data. Both methods yielded accurate results but the adiabatic mode method proved to be much faster than the parabolic equation method.